Predicting supermarket sales: the use of regression trees - Silva, A. L.; Cardoso, M. G. M. S. (Journal of Targeting, Measurement and Analysis for Marketing, 2005)
The performance of points of sale is influenced by multiple factors, including the characteristics of their external environment. The main focus of this study is the analysis of a supermarket chain store's external environment and its influence on the store's performance. Principal components analysis is used for data reduction of store attributes (eg visibility and accessibility). A regression tree is used for stores' sales prediction and clustering. The first tree branching divides smaller and larger stores. Factors like the stores' lack of visibility and heavy road traffic contribute especially to the decrease of sales in smaller stores. Factors like the availability of public transport and the absence of a specific competitor in the neighbourhood contribute to a better performance of larger points of sale. In addition to the insight it allowed concerning the performance of the existing stores, and notwithstanding some limitations (eg a static modelling approach is considered), the proposed tree model has been used successfully in predicting the performance of new stores.